PENINGKATAN POTENSI SITUS BERSEJARAH MELALUI SOSIAL MEDIA DI KELURAHAN URANG AGUNG KABUPATEN SIDOARJO - Khusnul Isma Nuriza; Bibi Ghoniyah; Ziyan Virdaus; Fahmul Hikam Al Ghifari (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2023)
The aim of this activity is to help the community of Urang Agung Subdistrict in promoting site-based tourism potential, namely the Sendang Agung spring and Mbah Mujarrod's grave. The method for this service is ABCD which prioritizes the potential or assets that exist in Urang Agung Village. The result is that the Urang Agung sub-district has tourist assets, namely the Sendang Agung site and the tomb of Mbah Mujarrod. These two potentials will be published on social media in the hope that they will become better known to the wider community, be noticed by several parties, and improve the economy of the residents of Urang Agung village. Considering that social media today plays an important role in almost every line of life. The team uses Instagram type social media considering it has more complete features starting from feeds, reels, stories and highlights.